Da li je pravo vreme za izgradnju velike solarne elektrane u Srbiji? - Rajaković, Nikola (Energija, ekonomija, ekologija : list Saveza energetičara, 2021)
According to almost all estimates, significant investments in new renewable energy sources in Serbia are needed. Serbia has economically viable potentials of renewable energy sources (RES) (solar energy, wind energy, hydropower, biomass energy, geothermal energy, etc.), so the structure of the production mix in the electricity system should increasingly be based on renewable sources. In this paper, an attempt is made to answer the following questions: does Serbia need new production capacities, does Serbia need new production capacities from RES, and finally, which of the RES would be the most suitable at the moment? The paper assesses whether this is exactly the right moment to accelerate the process of energy transition in Serbia, as well as the opportunity to ensure a more sustainable growth and development through a faster transition to RES. It starts from the fact that increasing the production of electricity from RES, together with measures to increase energy efficiency and decarbonize energy production and consumption, is the backbone of the energy transition and at the same time the essence of Serbia's commitments by joining the Energy Community and accepting international climate agreements. The paper assumes that by increasing the efficiency of the energy sector and use of RES, European policy goals can be achieved in Serbia and that energy sector can be positioned as an engine of stability and sustainable economic development. Secondary effects will lead to increased sustainable employment, reduced public debt and increased competitiveness of the sector. Therefore, the energy transition should be seen as a development opportunity. The construction of large RES plants, especially large solar power plants in Serbia and joining the EU Green Deal, is certainly a signal that Serbia is well on its way to developing a modern, environmentally friendly, competitive and regionally integrated energy system. This will trigger the necessary investments in the modernization of the energy sector and enable the attraction of foreign direct investments. Achieving this vision requires decisive political action at the national and regional levels. Solar projects have the lowest levelized costs of produced kWh of electricity, they are the fastest to implement and they have the least environmental and social impact. Also, large installed capacity can be achieved through a series of large and medium-sized projects that would be territorially distributed in order to reduce the simultaneity of production.